Will Eisner : a comics biography - Weiner, Stephen, 1955-; Mazur, Dan, 1959- (NBM Graphic Novels, 2025)
"Explore the life of Will Eisner, one of the most influential artists in the history of comics through the most appropriate medium: a graphic novel! From his immigrant roots and childhood in New York, starting his own comics studio and business, and the creation and publication of his beloved comic, The Spirit, through popularizing the term "graphic novel" as the result of trying to convince a general trade publisher to publish the groundbreaking A Contract with God, you'll follow along in Eisner's life journey"--